EKUITAS MEREK DAN IDENTIFIKASI MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK LOKAL ACARAKI: STUDI KASUS GENERASI Z DI JABODETABEK - Habibie, Ahmad; Kurniaty, Dewi (LP2M Universitas Bina Bangsa, 2025)
This research was conducted to find out the influence of brand equity and brand identification variables on the purchasing decisions of Acaraki Generation Z in Jabodetabek. Previous research found a positive influence of brand equity (indicators of awareness, association, brand loyalty, perceived quality, and locality) on purchasing decisions. Previous research did not specifically mention brand names, did not have demographic limitations, and did not include brand evaluation indicators, so the author decided to conduct this research. Data collection uses questionnaires distributed to obtain respondents. The sample obtained was 201 respondents, but using the criteria of Generation Z and being familiar with Acaraki resulted in the selection of 153 respondents who were ready to process the data. The testing technique uses the SPSS 30 application with validity, reliability, and descriptive testing then multiple linear analysis. Brand equity and brand identification variables (indicators of awareness, association, brand loyalty, perceived quality and locality, as well as brand evaluation) have a significant positive influence on the purchasing decision of Acaraki. Academically, this research can provide direction for further research regarding Generation Z's attitudes towards herbal medicine. Practically, it was found that the strength of the Acaraki brand lies in the indicators of brand awareness, perceived quality, brand associations and brand loyalty. So, it can be used for marketing direction for Generation Z.